Postmodernist Identity Construction and Consumption - ÇAĞLAR, İrfan; KARABABA, Reyhan (Journal of Economic Development, Environment and People, 2016)
Abstract. With the transition from modernism to postmodernism, identity as a concept has started to become redefined in sociology literature. The aim of this study is to show that postmodernism and symbolic interactionism are fused together to delineate both the scene as well as an actor’s identity. In that way, the interaction of a social structure with a culture that won’t be completely ignored, and, with the opinion that the categorized roles can skillfully be shaped and diversified by actors, it is possible to refrain from a pure determinism. But the transformation to enter different roles lacks meaning. Individuals pay more attention to their appearance more than who they are in order to be accepted by each group. In this manner, a metaphysical shell game begins. In the following study, the “Social Appearance Anxiety” was used as an indicator of this game. And to determine who is willing to play the game, cultural parameters were utilized. This study was based on the analysis of the data collected through two questionnaires given to 181 students studying at Hitit University. The INDCOL questionnaire [Singelis et al., 1995] measuring cultural values and “Social Appearance Anxiety” scale developed by [Hart, 2008] were used in the study.